PENGARUH FAKTOR-FAKTOR FUNDAMENTAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP HARGA SAHAM SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - kamilia alshifa (Accounting Global Journal, 2021)
Abstract: This research aimed to analyze the effect of Earning per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV), and Institusional Ownership (KI) on Stock Price of infrastructure, utility, and transportation companies in 2014-2018. Sampling was done by using purposive sampling method. Analysis used is panel data regression analysis using Eviews program version 9. The results show that in partially, Earning per Share (EPS) and Price to Book Value (PBV) have significantly affected on stock price, whereas Debt to Equity Ratio (DER) and Institusional Ownership (KI) have no significantly affected on stock price. Simultaneously, all the variables together have significantly affected on stock price. The coefficient of determination shown from adjusted R-Squared value of 0,4825. This means that the dependent variabel is 48,25% can be explained by the four independent variables, while the remaining 51,75% is explained by other factor outside this research model.Keywords : Earning per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV), Institusional Ownership (KI), Stock Price